The Influence Of Marketing Mix On Usage Decision Of Auto Clean Waterless Car Wash Services - Tegar Graha Adiwiguna; Megawati Simanjuntak; Kirbrandoko - (Jurnal Studi Manajemen dan Bisnis, 2021)
Increasing the number of vehicles makes a great business opportunity for car wash services. AutoClean Waterless is a company engaged in car wash services that utilise innovation by using special fluids so that it saves water. The problem faced by AutoClean in Bogor City is AutoClean’s sales have not been stable because there is still a decrease in transaction and termination of partners. Sample in this research were 185 respondents. Data were analysed using descriptive analysis and SEM LISREL. The result of this research shows that consumer use behaviour is influenced by weather, priority factors in using car wash services are quality, price, ease for access, and customers more often come to outlets that are not in the mall and majority customers use silver packages. Consumer perception of AutoClean innovation shows that innovation is one of the most essential factors in usage decisions of the consumer. The marketing mix (7P) has a significant influence on usage decisions. Marketing strategies to increase sales in AutoClean Waterless can be applied by making AutoClean customer segmentation based on customer characteristics. Then the company can make priority targets  following following predetermined segmentation. Next, AutoClean can make positioning by looking at the priority factors when customers choose car wash services, such as quality, price and ease of access